EPID-19. CONDUCTING A NATIONWIDE BRAIN TUMOR EPIDEMIOLOGY STUDY IN AN LMIC: A MULTI-INSTITUTIONAL EXPERIENCE. (12th November 2021) - Baig, Erum; Shah, Mashal; Bajwa, Mohammad Hamza; Laghari, Altaf Ali; Akhunzada, Naveed Zaman; Bin-Anis, Saad; Khalid, Usman; Qadeer, Namra; Lutfi, Areeb; Tahir, Izza; Bajwa, Rameen; Rashid, Huzaifa; et al.
Abstract: Very little research has been conducted on brain tumor epidemiology in Pakistan and a few studies that do exist provide regional data only. Conducting population based epidemiological studies in low-and-middle income countries (LMICs) like Pakistan can be particularly challenging due to limited resources, poor clinical and research infrastructure, unreliable or incomplete hospital records and a lack of standardization across the health care system. Population-wide studies and registries play an important role in cancer epidemiology and can help identify the current magnitude of cancer burden and its likely future evolution, allowing for better planning of prevention, diagnosis, management, and rehabilitation. This paper describes our experience in designing and conducting Pakistan Brain Tumor Epidemiology Study (PBTES), a first-ever nationwide study carried out to assess the distribution of brain tumors in Pakistan. In addition to the aforementioned obstacles, we were also faced with the global health crisis caused by the COVID-19 pandemic and had to promptly adjust our study accordingly. Other investigators conducting epidemiological studies in LMICs with similarly challenging and constricting settings could benefit from our experiences.